466. SARS-CoV-2 Diagnosis And Point Prevalence in a Non-Cohorted Tertiary Care Center. (31st December 2020) - Schrank, Spencer; McAleese, Katherine; Spence, Amanda B; Natarajan, Madhuri; Timpone, Joseph; Chang, Joseph; Balba, Gayle p; Kumar, Princy
Abstract: Background: The CDC recommends testing for SARS-CoV-2 in patients who present with symptoms consistent with COVID-19 and to cohort hospitalized patients diagnosed with COVID-19. Up to 35% of persons infected with SARS-CoV-2 are asymptomatic; however, no recommendations exist for universal testing in hospitalized patients. We assessed the point prevalence of SARS-CoV-2 infection amongst hospitalized patients at a tertiary care center during a time when there was a regional surge of cases. Methods: Nasopharyngeal SARS-CoV-2 PCR testing was performed on inpatients at Georgetown University Hospital on 4/27/20, excluding those who were SARS-CoV-2 positive, tested within 72 hours or admitted to pediatric, psychiatric, labor & delivery or ICUs. Patients within the hospital were not cohorted based on COVID-19 status. Patient demographics and comorbidities were obtained from the EMR and analyzed for significance based on SARS-CoV-2 status. Results: Hospital census on the testing date was 297; 204/297(68.7%) met inclusion criteria; 78/297(26.3%) were known COVID-19 patients. Within the study group 78/204 (38.2%) had known COVID-19, 21/204 (10.3%) were PUIs (4 of whom tested positive), 31/204 (15.1%) tested negative for COVID-19 within 72 hours and 74/204 (36.3%) met criteria for testing. The median age was 62 years (IQR, 53 to 70), 59%(n=122) were male, 56%(n= 115) were Black, and 90%(n=185) had at least one co-morbidity. 0/74 of those tested on 4/27/20 were positive for SARS-CoV-2, and none were diagnosed with COVID-19 within 28 days. In adjusted analyses, patients who were hospitalized for COVID-19 were more likely to be Black(OR=10.53 95% CI 3.02, 36.68, p=0.0002); male(OR=3.27 95% CI 1.26, 8.47, p=0.0143); reside in group/nursing homes(OR= 11.78 95%CI 3.03, 45.76, p=0.0004); have a history of prior stroke(OR= 6.25 95%CI 1.49, 26.12, p=0.012); but less likely to smoke(OR=0.10 95%CI 0.02, 0.48, p=0.0039), or have active malignancy (OR= 0.11 95%CI 0.01, 0.73, p=0.0223). Conclusion: The use of CDC testing criteria for PUIs were successful in identifying COVID-19 patients and limiting the need for routine testing in all hospitalized patients during a time when access to testing was limited. Nosocomial transmission did not occur in our institution despite a lack of cohorting. Disclosures: Princy Kumar, MD, Gilead Sciences Inc. (Scientific Research Study Investigator)